2010
DOI: 10.1038/onc.2010.192
|View full text |Cite
|
Sign up to set email alerts
|

The RASSF8 candidate tumor suppressor inhibits cell growth and regulates the Wnt and NF-κB signaling pathways

Abstract: The Ras-assocation domain family (RASSF) of tumor suppressor proteins until recently contained six proteins named RASSF1-6. Recently, four novel family members, RASSF7-10, have been identified by homology searches for RA-domain-containing proteins. These additional RASSF members are divergent and structurally distinct from RASSF1-6, containing an N-terminal RA domain and lacking the Sav/RASSF/Hpo (SARAH) domain. Here, we show that RASSF8 is ubiquitously expressed throughout the murine embryo and in normal huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 26 publications
3
90
0
Order By: Relevance
“…There is some evidence that RASSF7 expression is upregulated in certain cancers, hence it may promote cancer development, whereas the majority of the classical RASSF genes show loss of gene expression in tumors and exhibit tumor suppressor properties. There is increasing evidence that RASSF8 may act as a tumor suppressor gene in lung cancer; we have demonstrated that RASSF8 is essential for maintaining adherens junction function in epithelial cells and has a role in epithelial cell migration (Lock et al, 2010). Drosophila RASSF8 (dRASSF8) has been shown to interact with Drosophila ASSP (dASSP) and this interaction is conserved in mammals.…”
Section: Introductionmentioning
confidence: 97%
“…There is some evidence that RASSF7 expression is upregulated in certain cancers, hence it may promote cancer development, whereas the majority of the classical RASSF genes show loss of gene expression in tumors and exhibit tumor suppressor properties. There is increasing evidence that RASSF8 may act as a tumor suppressor gene in lung cancer; we have demonstrated that RASSF8 is essential for maintaining adherens junction function in epithelial cells and has a role in epithelial cell migration (Lock et al, 2010). Drosophila RASSF8 (dRASSF8) has been shown to interact with Drosophila ASSP (dASSP) and this interaction is conserved in mammals.…”
Section: Introductionmentioning
confidence: 97%
“…Collectively, these findings support the notion that RASSF8 regulates tumor development. Additional functions of RASSF8 include cell-cell adhesion due to its association with adherens junction linked to b-catenin/E-cadherin function [4]. Wound healing assays exhibited increased cell migration in cells lacking RASSF8 expression, suggesting that loss of RASSF8 may contribute to tumor aggressiveness [4].…”
Section: Rassf8mentioning
confidence: 99%
“…These proteins were named due to the presence of a Ras association (RA) domain in their N-terminus or C-terminus. The RA domain potentially interacts with the Ras GTPase family of proteins [2] that control a number of cellular processes including membrane trafficking, apoptosis, and proliferation [1][2][3][4][5]. Direct association with K-Ras has been only observed for RASSF2, 4, 5A, 6 and 9 [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…27) and RASSF8 (ref. 28), which are often downregulated in human colon cancers. However, for the known targets reported for BCLAF1, such as CCND1 and TP53, there were no significant changes observed after BCLAF1-L knockdown ( Supplementary Fig.…”
Section: Bclaf1-l Isoform Promotes Tumorigenesis Of Rko Cells In Micementioning
confidence: 99%